A BAYESIAN DESIGN TO TEST DOSE-RESPONSE SEQUENTIAL TRIALS USING ISOTONIC REGRESSION - SOUZA, Edcarlos Miranda de; CHAVES, Lucas Monteiro; MUNIZ, Joel Augusto; SOUZA, Devanil Jaques (Brazilian Journal of Biometrics, 2016)
The present work aims to achieve a dose with a pre-specified toxicity rate in a target population. It proposes, using Bayesian methods and isotonic regression, a sequential design to allow the researchers to update prior information. The theory behind the design is not easily assimilated to non-statisticians. What makes such approach attractive is its reduction to four steps of easy manipulation, without the need of computational effort. Simulation procedures confirm the effectiveness of the proposed methodology.